Afekt i defekt atlasu zwierząt. Narracyjny wymiar historii naturalnej w malarstwie Waltona Forda - Schollenberger, Justyna (Zoophilologica. Polish Journal of Animal Studies, 2016)
This paper aims at the problem of realism in the artistic representation of animals. Contemporary animal studies recognize the problem of narratives in which animals serve as a negative point of reference to humans or as a symbol, always referring to some cultural story. In this context the anthropocentric art of Walton Ford is particularly interesting. The painter is openly enthusiastic about the symbolic and narrative uses of animals in culture, and yet in his paintings he manages to represent animals’ otherness, and their ability not to be „tamed” by our schemes.